c.1 - Hooja, Rakesh (ed.) (New Delhi, 2008)
This book tell us about the working of Collectors in different parts of the country at different points of time, the problems and challenges faced by them, the various changes in their roles and functions and societies expectations from them, etc.
Keywords: District governance